The Application of Dose-Response Models to Determine the Median Effective Adsorbent Bone Char Dose to Remove Fluoride From Drinking Aqueous Solutions - Sara Zebarjadi (پزشکی بالینی ابن سینا, 2016)
Introduction: In studies of the adsorption of pollutants onto different adsorbents, determining the adsorbent dose of the most important characteristics must be considered. The aim of the study was the determination and modeling of dose-response bone char fluoride removal from aqueous solutions and comparison of the adsorption isotherm models with dose-response models from the perspective of adsorption.